Gurdon Saltonstall correspondence - Saltonstall, Gurdon, 1708-1785.
ALS (1776 September 23) written by Saltonstall to Jonathan Trumbull describing troop movements, casualties, and other aspects of campaigns in New York, New Jersey, and Pennsylvania during the Revolution.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Trumbull, Jonathan, -- 1740-1809 -- Correspondence; United States. -- Continental Army; New Jersey -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; Pennsylvania -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Campaigns; United States -- History -- Revolution, 1775-1783 -- Casualties; Army officers